Antifungal activity of turmeric rhizome extract against Ganoderma boninense - Karlina, Lidya; Suwandi, Suwandi; Muslim, A.; Damiri, Nurhayati; Rohim, Abdul Madjid; Negara, Zaidan P. (Journal of Scientific Agriculture, 2024)
Basal stem rot (BSR) caused by Ganoderma boninense threatens the oil palm industry, particularly in Southeast Asia. This study evaluated methanol extracts of turmeric rhizome (TRE) from four ecotypes (Bangka, Bandung, Palembang, and Surabaya) for antifungal activity against G. boninense. TRE showed strong inhibition, with a minimum inhibitory concentration (MIC) of 0.31% and IC50 values between 0.93% and 1.92%, exhibiting dose-dependent effects. Treated fungal hyphae displayed morphological abnormalities with enhanced chitin and protein deposition. Elevated electrical conductivity in fungal culture media indicated membrane damage and leakage of intracellular contents. These findings highlight the potential of TRE as a sustainable alternative to chemical fungicides for BSR management.